Ability of the Mandarina Bavaria hop variety to release free odorant polyfunctional thiols in late‐hopped beers. Issue 2 (27th January 2021) - Chenot, Cécile; Collin, Sonia
Abstract : The cysteinylated and glutathionylated precursors of 3‐sulfanylpentanol (Cys‐3SPol up to 197 μg/kg, G‐3SPol up to 14 mg/kg), recently reported in hops, were quantitated for the first time in the Mandarina Bavaria variety, along with the ubiquitous cysteinylated and glutathionylated forms of 3‐sulfanylhexanol (Cys‐3SHol up to 897 μg/kg, G‐3SHol up to 46 mg/kg). In contrast to findings with another new German cultivar, Polaris, no trace of 3‐sulfanyl‐4‐methylpentanol adducts (Cys‐ and G‐ 3S4MPol) was found. To assess the transfer rate of thiols from hops to finished beer, the same pilot Mandarina Bavaria hopped wort was fermented with two different dry yeasts, bottle refermented or not, and analysed. The data were compared with results obtained for a similarly produced commercial beer. In conclusion, despite significant variation between harvest years, Mandarina Bavaria appears not to contain outstanding amounts of free thiols or thiol S‐conjugates. Its S‐conjugate pool is sufficient, however, to bring 3SHol above its odour threshold. This work also suggests that since 3S4MPol was found near or above its threshold in most late‐hopped beers it does not originate from hops and that malt may be its main contributor. © 2021 The Institute of Brewing & Distilling